A Mobile-Based Network Tools Information System to Enhanced Connectivity and Security - Rosalina, Rosalina; Sahuri, Genta; Nanda, Yovalentino Aprilian Wijaya (Journal of Information System and Informatics, 2024)
This paper addresses the common challenges faced by network administrators in managing and troubleshooting network issues. Traditional desktop-based network management tools often restrict mobility and responsiveness, hindering the ability to address network problems promptly. To address these limitations, this study presents the development of a mobile-based network tools information system. The proposed solution integrates various network management functionalities into a mobile application, enabling administrators to monitor, diagnose, and resolve network issues remotely. Employing a design and implementation approach, the research includes user requirements analysis, system design, and rigorous testing. Results show significant improvements in response times and diagnostic accuracy. User feedback highlights high satisfaction with the system's functionality and ease of use. Overall, the mobile-based network tools information system offers a versatile and effective solution for network management, enhancing operational efficiency and responsiveness in diverse network environments.